Functional Inverse Material Description Test: Development of Islamic Integrated Communication Ability Instruments - Laila, Alfi Rachma Nisfi; Cholily, Yus Mochamad; Syaifuddin, Mohammad; Kurniawati, Wiwit; Rahman, Anisur (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
Assessment activities are crucial to measuring learning success in the school system. Assessment can be used to improve education where teachers incorporate Islamic beliefs. This study explains how to create a religiously-integrated mathematical communication skills test. This is ADDIE model development research. The research was tested at a Tulungagung Madrasah Aliyah. The data-gathering method solves ten inverse function math questions using a description test. Data analysis uses strength, reliability, validity, and difficulty. This study found that the social essay exam instrument analyses high school students' mathematics communication skills and Islamic beliefs, with 7 items valid and reliable and 3 items removed. This study found that the Islamic integrated mathematical communication ability test is valid, reliable, discriminatory, and somewhat demanding.